2020
DOI: 10.33394/bjib.v8i1.2697
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Worksheet Inkuiri Terintegrasi Kearifan Lokal Untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa

Abstract: The purpose of this study was to assess the effectiveness of integrated local wisdom sheets for local wisdom on students' critical thinking skills. This type of pre-experimental research with the design of one groups pre-test post-test design. Samples were 18 students taken with saturated sampling technique. The instrument used was the Critical Thinking Skills Test (TKBK) with indicators: 1) interpretation; 2) analysis; 3) conclusions; 4) evaluations; 5) explanations; and 6) self-regulation. Data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…This is because necessary thinking skills need reasons that can strengthen the acceptance of something. Hunaepi et al (2020) argue that critical thinking is essential to be trained in the learning process so that students have the provision of critical, innovative, and creative thinking.…”
Section: Resultsmentioning
confidence: 99%
“…This is because necessary thinking skills need reasons that can strengthen the acceptance of something. Hunaepi et al (2020) argue that critical thinking is essential to be trained in the learning process so that students have the provision of critical, innovative, and creative thinking.…”
Section: Resultsmentioning
confidence: 99%
“…Learning materials based on local wisdom in the traditional game of tajog in accordance with research conducted by [7] found that the development of science modules based on local wisdom on business and energy materials is effective for improving student learning outcomes and learning activities. [8] found that the development of local wisdom-based physics student books was feasible and easy to understand by students, and [9] the implementation of local wisdom-integrated inquiry worksheets could improve students' critical thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…20 Tahun 2003 tentang sistem pendidikan nasional pasal 36 ayat 3 bahwa kurikulum yang digunakan dalam proses pembelajaran harus memperhatikan salah satunya yaitu potensi daerah dan lingkungan tempat tinggal peserta didik. Sebagaimana amanah undang-undang tersebut maka pembelajaran harus berbasis keunggulan lokal (Hunaepi et al, 2020). Berdasarkan hal di atas, kearifan lokal dapat dijadikan sebagai salah satu cara untuk menjalankan kurikulum 2013 yang memiliki karakteristik pengaplikasian pendidikan yang diperoleh peserta didik di sekolah pada lingkungan masyarakat.…”
Section: A Latar Belakangunclassified